2021
DOI: 10.3390/nu13092978
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Dietary Data into Microbiome Studies: A Step Forward for Nutri-Metaomics

Abstract: Diet is recognised as the main driver of changes in gut microbiota. However, linking habitual dietary intake to microbiome composition and activity remains a challenge, leaving most microbiome studies with little or no dietary information. To fill this knowledge gap, we conducted two consecutive studies (n = 84: a first pilot study (n = 40) to build a web-based, semi-quantitative simplified FFQ (sFFQ) based on three 24-h dietary recalls (24HRs); a second study (n = 44) served to validate the newly developed sF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…51 Depletion of Faecalibacterium is thought to be associated with pre-obesity and obesity (BMI > 25), suggesting a link with energy metabolism. 52 Interestingly, f_Veillonellaceae was elevated upon treatment in our experiments (Fig. S7A and B†).…”
Section: Resultsmentioning
confidence: 56%
“…51 Depletion of Faecalibacterium is thought to be associated with pre-obesity and obesity (BMI > 25), suggesting a link with energy metabolism. 52 Interestingly, f_Veillonellaceae was elevated upon treatment in our experiments (Fig. S7A and B†).…”
Section: Resultsmentioning
confidence: 56%
“…For bacterial and fungal microbiome analysis, 34 fecal samples (FCs) were collected from HCs from a previous study [ 30 ], 83 rectal swabs from ICU-COV(−), and 86 RSs and 78 TAs from ICU-COV(+) patients. A total of 281 gut and respiratory samples were collected for bacterial and fungal microbiome analysis and 53 blood samples were obtained from ICU-COV(+) patients for measuring the levels of IgM, IgG, and IL-6.…”
Section: Methodsmentioning
confidence: 99%
“…Six volunteers, free of diagnosed diseases, were recruited between August 2021 and October 2021 by disseminating an announcement. During two months, each volunteer lled an sFFQ [32], in total 12 sFFQs were collected.…”
Section: Collection and Processing Of Habitual Diet Informationmentioning
confidence: 99%
“…This protocol has been validated on a cohort of 48 fecal samples collected from six healthy volunteers longitudinally within eight weeks. Beyond that, we also collected the habitual diet data by asking the volunteer to ll out a short food frequency questionnaire [32] every four weeks. Our study demonstrated that after applying this enrichment protocol, signi cantly more fungal sequences could be captured with normal-depth shotgun sequencing.…”
Section: Introductionmentioning
confidence: 99%